1998
DOI: 10.1016/s0029-7844(98)00125-2
|View full text |Cite
|
Sign up to set email alerts
|

Amniocentesis-Related Fetal Loss: A Cohort Study

Abstract: Second-trimester amniocentesis is probably not associated with a greater fetal loss rate than that of matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 4 publications
5
39
2
Order By: Relevance
“…A study conducted in Turkey found, in contrast to the findings of this study, high screening test results to be 54.9%, advanced maternal age to be 20%, and abnormal USG findings to be 16% (10). Tongsong et al, in a 1998 study, differed dramatically in their findings and reported advanced maternal age to be 86% (11). It is striking that in our study the acceptance rate of advanced maternal age as an indication was reduced and that it was screening tests and ultrasound findings that led to the prenatal diagnosis.…”
Section: Discussioncontrasting
confidence: 57%
“…A study conducted in Turkey found, in contrast to the findings of this study, high screening test results to be 54.9%, advanced maternal age to be 20%, and abnormal USG findings to be 16% (10). Tongsong et al, in a 1998 study, differed dramatically in their findings and reported advanced maternal age to be 86% (11). It is striking that in our study the acceptance rate of advanced maternal age as an indication was reduced and that it was screening tests and ultrasound findings that led to the prenatal diagnosis.…”
Section: Discussioncontrasting
confidence: 57%
“…The association was statistically significant and similar for spontaneous preterm delivery and induced preterm delivery. On the contrary, other studies 13,39 have shown no difference in the rate of preterm delivery after amniocentesis.…”
Section: Preterm Deliverymentioning
confidence: 80%
“…In the same study, early membrane rupture was determined in only 2 cases [14]. In another similar case-controlled study, Tongsong et al compared cases who had and had not undergone amniocentesis, no statistically significant difference was determined between the groups in respect of fetal loss, placental abruption or premature birth [16]. In a study by Müler et al, there was reported to be a statistically significantly higher rate of premature birth at 24-28 weeks in the group that had undergone amniocentesis compared to the control group [15].…”
Section: Discussionmentioning
confidence: 96%